Rancang Bangun Sistem Rekomendasi Resep Masakan Khas Indonesia Menggunakan Metode Collaboration Collective Intelligence dan Slope One - Adhi Kusnadi; Daniel Daniel (Ultimatics : Jurnal Teknik Informatika, 2017)
Today, recipes are not just physical, but some are digital. So users do not have to store recipe books that have been purchased to find recipes for a dish. One of a website providing recommendations for digital recipe guides is dapursaji. This application helps users to search for recipes only by entering the ingredients of the food owned by the user. And will produce a list of dishes that use the material entered by the previous user. In addition there will be related recommendations after opening one of the recipes after the search. Not only that, this website can also provide the freedom to innovate, by means of all users can fill a new recipe in accordance with the innovation and creation itself. Then the recipe will be published and read by the public. Collaborative Collective Intelligence and Slope One methods are implemented in this design, and evaluation results show that as many as 89% of users surveyed have been satisfied with the suitability and usefulness of the built system. Index Terms—recipes, dish, collaborative Collective Intelligence, slope one